2017
DOI: 10.1177/000203971705200206
|View full text |Cite
|
Sign up to set email alerts
|

Press Freedom and Nigeria's Cybercrime Act of 2015: An Assessment

Abstract: This study assesses the Cybercrime Act 2015 and its implications for online press freedom in the liberal authoritarian state of Nigeria. Specifically, the study examines how the character of political leadership in Nigeria leads to wrongful application of the act to undermine the independence of the press. The study shows that Nigeria's online press freedom index has consistently worsened since the introduction of the Cybercrime Act in 2015, and it recommends the promotion of a holistic democratic project that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…However, there are still discussions about entrepreneurship in Nigeria as there are more grounds to cover where the standpoint is and the direction to move. The government's credibility is also questioned since many political in uences have worsened Nigeria's social and economic status (Orji, 2014) through unlawful practices like violence, press, and press captivity (Adibe et al, 2017;Eke, 2015). Ogunyemi (2014) stresses the o cial corruption in his analysis of nancial records in the decolonization period, stating that traces of corruption in Nigeria could be tracked for decades, and now it has strengthened the roots.…”
Section: Theoretical Approachesmentioning
confidence: 99%
“…However, there are still discussions about entrepreneurship in Nigeria as there are more grounds to cover where the standpoint is and the direction to move. The government's credibility is also questioned since many political in uences have worsened Nigeria's social and economic status (Orji, 2014) through unlawful practices like violence, press, and press captivity (Adibe et al, 2017;Eke, 2015). Ogunyemi (2014) stresses the o cial corruption in his analysis of nancial records in the decolonization period, stating that traces of corruption in Nigeria could be tracked for decades, and now it has strengthened the roots.…”
Section: Theoretical Approachesmentioning
confidence: 99%
“…The scope and span of the debate is impressive, largely due to the historic implications of the information age and the complexity of democratic governance (Weare, 2002). The study of the relationship between internet and democracy has engaged many researchers using different approaches from conceptual and theoretical (Weare, 2002; Margetts, 2013; Grofman et al , 2014; Adibe et al , 2017; Mustapha, 2017; Ruijgrok, 2017) to empirical (Best and Wade, 2009; Nisbet et al , 2012; Salgado, 2012; Lee, 2017; Nam, 2017; Pirannejad, 2017; Shen, 2017; Evans, 2018a).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, democratization and internet usage is found to moderate the relation between internet usage and demand for democracy. Adibe et al (2017) assessed the Cybercrime Act 2015 and its effects on online press freedom in the Nigerian liberal authoritarian state. Examining how Nigerian political leadership wrongfully applied the act to undermine press independence, the authors found that Nigeria’s online press freedom has steadily worsened since the 2015 Cybercrime Act.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations